Social Media Influencers’ Role on Brand Engagement, Value, and Consumers' Intention to Buy Muslim Fashion - Labika Yuyun Erdiyana; Istyakara Muslichah; Rika Mulia; Alldila Nadhira Ayu Setyaning (Universitas Muhammadiyah Yogyakarta, 2022)
This study examines the effect of the perceived influence of digital influencers on the purchase intention of brand recommendations by influencers who influence their followers. This research has two mediating variables: brand attachment in self-concept and expected brand value. This type of research is quantitative research, and the method used is convenience sampling with the criteria that respondents have followed the Instagram accounts of Muslim fashion brand digital influencers aged 18-27 years old and living in Indonesia. The method used is an online survey and sharing on their social media. The total sample used for this study was 150 respondents. The final results of this study indicate that perceived influence positively impacts brand engagement, brand expected value, and intention to buy recommended brands. Besides that, brand engagement also influences brand expected value. Lastly, both brand engagement and brand expected value positively impact the intention to buy the recommended brand.